3D spheroid models for in vitro evaluation of nanoparticles for cancer therapy - Tchoryk, Aleksandra (2018)
Many different nanoparticle delivery systems have been reported as potential cancer therapeutics, however, the tumour penetration and uptake characteristics have been determined for very few systems. Animal models are effective for assessing tumour localisation of nanosystems, but difficult to use for studying penetration beyond the vasculature. In this work, defined HCT 116 colorectal cancer spheroids were used to study the effect of nanoparticle size and surface modifications on their penetration and uptake. Incubation of spheroids with Hoechst 33342 resulted in a dye gradient which facilitated discrimination between the populations of cells in the core and at the periphery of spheroids by flow cytometry based on the degree of Hoechst staining. This model was used to compare doxorubicin and Doxil, a range of model polystyrene nanoparticles in different sizes (30 nm, 50 nm, 100 nm) and with different surface chemistry (50 nm unmodified, carboxylated, aminated) and polyethylene glycol modified NPs prepared from a promising new functionalized biodegradable polymer (poly(glycerol-adipate), PGA). Unmodified polystyrene nanoparticles (30 nm/50 nm) were able to penetrate to the core of HCT 116 spheroids more efficiently than larger polystyrene nanoparticles (100 nm). Penetration was also dependent on surface charge. PGA NPs of 100 nm showed similar penetration into spheroids as 50 nm polystyrene nanoparticles, and PEG surface modification significantly improved penetration into the spheroid core. The new spheroid model with Hoechst staining is shown to be a useful model for assessing NPs penetration and demonstrates the importance of controlling physical properties when designing nanomedicine.